Englishness : twentieth-century popular culture and the forming of English identity - Featherstone, Simon, 1960- (Edinburgh University Press, 2009)
This book examines the conflicts, dilemmas and contradictions that marked Englishness as the nation changed from an imperial power to a postcolonial state. The chapters deal with travel writing, popular song, music hall and variety theatre, dances, elocution lessons, cricket and football, and national festivals, as well as literature and film. ́⁰High́⁰₉ and ́⁰₈populaŕ⁰₉ cultures are brought together in dialogue, and the diversity as well as the problematic nature of English identity is emphasised. The case studies are linked by their interests in different kinds of performances of being English, and by a particular focus upon the voice and the body as key sites for the struggles of modern England. The book is a lively contribution to current interdisciplinary debates about Englishness, national cultures and postcolonial identities. It is relevant to undergraduate students of literature, drama, film, politics and sociology, and will also appeal to a general readership. Key Features*Wide-ranging survey of twentieth-century English cultures*Innovative attention to popular cultures*New development of postcolonial theories*Clear, accessible writing*Concise and varied case studies